Building an inclusive South African society: The position of young, white Afrikaans speaking women - Rauch, Lidia (University of Cape Town, 2020)
Globally, white people enjoy historical, unearned privilege. This phenomenon is known and understood as 'white privilege'. In contemporary South Africa, white privilege stems from colonialism and apartheid. The legacy of colonialism and apartheid is still felt today and has a direct and continuous consequence in the form of racial inequality. This dissertation confronts the legacy of Afrikaner nationalism, which essentially instituted and upheld apartheid and still undergirds white people's privilege in democratic South Africa. Engagements were undertaken with ten white, Afrikaans speaking women between the ages of 24 and 32. Substantive transformation, bringing about the necessary change to racial power relations, has not been realised in contemporary South Africa. The research finds that this phenomenon is a result of a 'reconciliation gap' that was left by the participants' parents' generation. It is argued that reconciliation in South Africa will only be possible if responsibility is taken for the wrongs of the past. A 'responsibility gap', left by the participants' parents' generation, is identified and the research findings suggest that this gap should now be covered by the post-apartheid generation. This generation must cover the gap and shoulder the responsibility that was not taken by their parents' generation. An inclusive innovation praxis model was produced, to suggest practical steps aimed at cultivating positive political agency and to cover the 'responsibility gap' and contribute towards a more inclusive South African society.